2011
DOI: 10.1080/00220671003690130
|View full text |Cite
|
Sign up to set email alerts
|

Should Students Be Allowed to Miss?

Abstract: In this paper we investigate the effect of class attendance on academic performance, and evaluate the existence and importance of minimum attendance requirement thresholds.We found that attendance has a relevant and statistically significant impact on performance, together with the existence of a threshold, although contrary to the expected, not associated with a decrease in performance, which questions the existence of minimum attendance requirement. JEL Classification: I21, I28

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Private enrollment has risen dramatically, from 15.1% in 1981 to 61.2% in 2017 (Centro de Estudios Mineduc, 2017; Verger, Bonal, & Zancajo, 2016b). Nowadays, around 90% of students in primary and secondary education are enrolled in schools funded through the voucher system (Paredes & Ugarte, 2011). On the other hand, private schools are allowed to operate on a for-profit basis and, since the mid-1990s, private subsidized schools have been allowed to charge families mandatory fees (Elacqua, Montt, & Santos, 2013) 3 .…”
Section: The Case Of Chile: Privatization Marketization and Inequalimentioning
confidence: 99%
“…Private enrollment has risen dramatically, from 15.1% in 1981 to 61.2% in 2017 (Centro de Estudios Mineduc, 2017; Verger, Bonal, & Zancajo, 2016b). Nowadays, around 90% of students in primary and secondary education are enrolled in schools funded through the voucher system (Paredes & Ugarte, 2011). On the other hand, private schools are allowed to operate on a for-profit basis and, since the mid-1990s, private subsidized schools have been allowed to charge families mandatory fees (Elacqua, Montt, & Santos, 2013) 3 .…”
Section: The Case Of Chile: Privatization Marketization and Inequalimentioning
confidence: 99%
“…The extent to which teaching or school quality characteristics can influence achievement outcomes, however, depends on the quantity of such schooling received. Studies across multiple countries have shown that higher rates of absence are associated with lower achievement, including in the United States (Roby, ; Schagen et al ., ; Gottfried, , , ), the United Kingdom (Malcolm et al ., ; Department for Education and Skills, ; Carroll, ), Australia (Hancock et al ., ; Daraganova et al ., ) and others (Fergusson et al ., ; Llie & Lietz, ; Paredes & Ugarte, ). In recent years, more advanced studies have used econometric techniques to imply causal relationships (Gottfried, , ).…”
Section: Introductionmentioning
confidence: 99%
“…Although over 40,000 studies on pedagogy have been published, very few have examined the effect of class attendance on examination performance. The results of studies that have measured attendance and performance have varied, with some showing a definitive benefit to class attendance and others none . The settings and populations of these studies have been diverse, and their results may not necessarily be applicable to medical school education.…”
Section: Introductionmentioning
confidence: 99%